Putting God in God's Place: Does Theology Belong in the University?. (September 2016) - Stackhouse, John G.
Should theology be a part of the Great Conversation of the modern university? Oxford and Cambridge employ theologians while in Australia theology is utterly unknown in any reputable secular university. Harvard, Yale, and Chicago maintain divinity schools while Princeton, Stanford, and the best public institutions in America keep theology resolutely on the margins—in student clubs and chaplaincies. Canadian universities present a widely varying spectrum from coast to coast. This article explores why there is ambiguity and ambivalence over such an ancient discipline, particularly dealing with critiques in the name of "scientific" rigour. It shows how theology and the public university can be mutually beneficial so long as each abides by its authentic norms.